Ricky Ricotta's Mighty Robot : Ricky Ricotta #1 - Pilkey, Dav, 1966-; Santat, Dan (New York, NY : Scholastic Inc., 2014)
Ricky Ricotta, a small mouse, is being bullied at school, but when he rescues a powerful robot from its evil creator, he acquires a friend and protector--and saves the city from Dr. Stinky.
"1"--Spine.
Keywords: Mice -- Juvenile fiction; Robots -- Juvenile fiction; Bullying -- Juvenile fiction; Heroes -- Juvenile fiction; Mice -- Fiction; Robots -- Fiction; Bullying -- Fiction; Heroes -- Fiction